Identification of lipid regulatory genes modulated by polyherbal formulation in chicken liver tissues using transcriptome analysis - Marimuthu, Saravanakumar; Suresh, Subramaniyam; D’Souza, Prashanth (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: To elucidate the cellular mechanisms of polyherbal formulation [Kolin PlusTM (KP)], genomics was performed to delineate the genes and pathways associated with lipid regulation through transcriptional profiling of the liver in commercial broilers raised on diets deficient in choline chloride (CCL). Materials and Methods: The gene expression patterns were studied for four groups [normal diet: normal, choline chloride deficient (CCD), KP (400 gm/ton), and CCL (400 gm/ton)] using Agilent microarray on day 42. The hierarchical cluster analysis was carried out on 12,614 differentially expressed genes (DEGs) with a similar expression. Results: Out of 12,614 significant DEGs, 1,926, 448, and 1,330 genes were expressed at higher rates, and 413, 482, and 1,364 were expressed at lower rates than CCD (CCD vs. normal), CCL (CCL vs. CCD), and KP (KP vs. CCD), respectively. GO enrichment analysis of DEG further revealed the significant association of biological process items with the lipid, sterol, and lipoprotein metabolic processes. In particular, peroxisome proliferator-activated receptor gamma coactivator 1 alpha, carnitine palmitoyl transferase I, hydroxyacyl-CoA dehydrogenase trifunctional multienzyme complex subunit beta, and patatin-like phospholipase domain containing 2 genes involved in fatty acid oxidation and lipase C, ABCG5, ABCG8, acetyl-CoA carboxylase, ATP citrate lyase enzyme, and peroxisome proliferator-activated receptor gamma genes involved in lipogenesis were altered by KP intervention for lipid metabolism. Conclusions: These findings reveal that the supplementation of KP prevents fatty liver-associated problems in broiler chickens by modulating the expression of the above-mentioned genes that are responsible for the oxidation of fatty acids and lipogenesis in the liver. J. Adv. Vet. Anim. Res., 9(3): 432–439, September 2022 http://doi.org/10.5455/javar.2022.i611